PENGELOLAAN LIMBAH PADA FASILITAS PELAYANAN KESEHATAN (STUDI DI UNIT PELAKSANA TEKNIS UNEJ MEDICAL CENTRE) - Khoiron, Khoiron (IKESMA, 2010)
Health-care waste includes all the waste generated by health-care establishments, research facilities, and laboratories. The waste produced by health-care providers are non-risk  (domestic waste) and risk  (infectious waste).   The waste produced in the course of health-care activities carries a higher potential for infection and injury than any other type of waste. The study was conducted to explain the waste management in health care facility. The study is descriptive research  used cross sectional design. The Results showed that solids, liquids, and little gases waste are  produced by Technical Organizing Unit Unej Medical Centre. Solid waste treatment is operated by separation infectious and domestic waste, than they are  removed and combusted in incenerator at TPA Pakusari. Liquid waste treatment is operated by saptic tank. Keywords : Waste, Management, Health care fasility